Does Size Outweigh Number in Predicting Survival After Pulmonary Metastasectomy for Soft Tissue Sarcoma? Insights from a Retrospective Multicenter Study - Burkhard-Meier, Anton; Grube, Matthias; Jurinovic, Vindi; Agaimy, Abbas; Albertsmeier, Markus; Berclaz, Luc M.; Di Gioia, Dorit; Dürr, Hans Roland; von Eisenhart-Rothe, Rüdiger; Eze, Chukwuka; Fechner, Katja; Fey, Emma; et al. (Annals of Surgical Oncology, 2025)
Background: Pulmonary metastasectomy (PM) is the most frequently performed local ablative therapy for leiomyosarcoma (LMS), synovial sarcoma (SyS), and undifferentiated pleomorphic sarcoma (UPS). This study aimed to assess surgical feasibility, outcome, and clinical prognostic factors, as well as the value of a peri-interventional systemic therapy. Methods: This multicenter retrospective study enrolled 77 patients with LMS, SyS, or UPS who underwent first-time complete resection of isolated lung metastases between 2009 and 2021. Disease-free survival (DFS), overall survival (OS), and clinical prognostic factors were analyzed. Results: After the first PM, the median DFS was 7.4 months, and the median OS was 58.7 months. A maximal lesion diameter greater than 2 cm was associated with reduced DFS in both the univariable (hazard ratio [HR], 2.29; p = 0.006) and multivariable (HR, 2.60; p = 0.005) analyses. The univariable analysis identified a maximal lesion diameter greater than 2 cm as an adverse prognostic factor for OS (HR, 5.6; p < 0.001), whereas a treatment-free interval longer than 12 months was associated with improved OS (HR, 0.42; p = 0.032). The addition of systemic therapy was associated with a trend toward improved DFS for patients with lesions larger than 2 cm (HR, 0.29; p = 0.063). Severe postoperative complications (grade ≥IIIa) occurred in 2 % of the patients. Conclusion: The size of resected lung metastases might be a more relevant prognostic factor than their number for patients with LMS, SyS, or UPS. For patients with lung metastases larger than 2 cm in maximal diameter, additional systemic therapy may be warranted.
CRIS-Team Scopus Importer:2025-05-30
Keywords: Undifferentiated pleomorphic sarcoma; Leiomyosarcoma; Metastasis; Pulmonary metastasectomy; Soft tissue sarcoma; Synovial sarcoma; Systemic therapy